IMPLEMENTASI STRATEGI KOMUNIKASI MANAGEMENT ARTIS GRUP BAND STARS AND RABBIT DALAM MEMPROMOSIKAN CONSTELLATION ASIA TOUR 2015 - Catur Priyadi; Rendy Dwi Saputra (Jurnal Pustaka Komunikasi, 2019)
The purpose of this study was determine to the implementation of communications strategies artist management bands Stars and Rabbit in promoting Constellation Asia Tour 2015. This study is applied constructivist paradigm, descriptive qualitative approach with case study method. Concepts and theories used in this research is. PR Management Theory, 7C's Communication and Concept 4 steps. The results of this study, based on the concept of four steps the management of the artist first an analysis performed of the attitudes and behavior of the audience, the process of planning promotions in the form of concert music is become desire of the management of the artist and the artist himself, Selection of communication used more priority to effectiveness and comfort of the side communicating in evaluation process will provide benefits for the parties concerned to predict the problems that may arise in the future. Media campaign that is frequently used is a social media and media partners, content or the content of the message to be conveyed to the audience in one place will have a different effect if the content of the message delivered at other places, the promotion is a ceaseless innovation, and channels used in communications strategy to promote the band Stars and Rabbit namely digital media.